2019
DOI: 10.1557/adv.2019.366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Time Current Annealing to the Hysteresis in CVD Graphene on SiO2

Abstract: Graphene specimens produced by chemical vapor deposition usually show p-type characteristics and significant hysteresis in ambient conditions. Among many methods, current annealing appears to be a better way of cleaning the sample due to the possibility of in-situ annealing in the measurement setup. However, long-time current annealing could increase defects in the underlying substrate. Studying the hysteresis with different anneal currents in a graphene device is, therefore, a topic of interest. In this exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Yu et al 18 also reported the formation of p-n junction in graphene via this electrical stressing-voltage-method and they reported that mobility improvement is realized by reducing the impurity induced scattering in graphene as a result of low level stressing voltage 18 . Therefore, this stressing-voltage-technique has also been applied to improve the quality of graphene based devices 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al 18 also reported the formation of p-n junction in graphene via this electrical stressing-voltage-method and they reported that mobility improvement is realized by reducing the impurity induced scattering in graphene as a result of low level stressing voltage 18 . Therefore, this stressing-voltage-technique has also been applied to improve the quality of graphene based devices 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%